Conference report: Second annual young researcher forum of the Japan Society of Medical and Pharmaceutical Sciences for Traditional Medicine. Issue 2 (11th August 2022) - Yoshino, Tetsuhiro; Yoneda, Taichi; Yang, Ximeng; Nishihara, Masakazu; Ogawa, Keiko; Kitamura, Masashi; Ando, Hirokazu; Nakashima, Souichi; Horie, Ichiro
Abstract: Five young researchers presented their studies in the field of traditional Japanese herbal medicine (Wakan‐yaku) at the second annual young researcher forum entitled "Growing Research Buds by Young Investigators, " held during the annual meeting of the Japan Society of Medical and Pharmaceutical Sciences for Traditional Medicine 2021. Mr. Yoneda presented exploratory research on new pharmaceutical seed compounds from garlic ( Allium sativum ). Dr. Yang investigated whether diosgenin promoted proper axonal regeneration in the brain using a mouse model of Alzheimer's disease. Her study clarified the molecular mechanisms of the diosgenin‐driven accurate pathfinding of injured axons. Mr. Nishihara presented his research on promoting the effective utilization of Phellodendron trees in Nara Prefecture. His research team evaluated the possibility of short‐term cultivation, screened for useful components in the leaves. Dr. Ogawa used the Japanese Adverse Drug Event Report (JADER) database, which contains reports of side effects associated with drug treatment, to demonstrate the effectiveness of hokizai in reducing side effects, particularly those of anticancer drugs. Dr. Kitamura reported that Cnidium monnieri (L.) Cusson fruit extract and the isolated active ingredients, osthol and imperatorin, strongly inhibited the activity of furin‐like enzymes. Further screening indicated that root extracts of Paeonia lactiflora Pall. and Scutellaria baicalensis Georgi suppressed cell syncytial formation by the S protein. The event was held online, and we had 86 participants. We can improve this forum in terms of format, frequency, and publicity activities; however, we hope to hold this forum in 2022 and in the future.